The relationship between serum adiponectin and resistin levels, insulin resistance and colorectal adenomas - Nazlı Demir,; Emel Ahıshalı,; Can Dolapçıoğlu,; Şerif Ercan,; Asuman Orçun Kaptanağası,; Reşat Dabak,; Nihal Yücel,; Mehmet Sargın,; Oya Uygur Bayramiçli, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The relationship between adipocytokines and the development of colorectal cancer is well-documented. Our aim was to assess the relationship among serum adiponectin and resistin levels, insulin resistance, and colorectal adenoma to evaluate whether these parameters can be used as biomarkers to predict the development of colorectal adenoma. Materials and Methods: This is a cross-sectional case-control study conducted in 32 patients with colorectal adenoma and 30 control subjects. Serum adiponectin and resistin levels, body mass index values, waist and hip circumferences and Homeostasis Model Assessment scores were measured. Results: Resistin levels were slightly higher and adiponectin was slightly lower in patients with colorectal adenoma compared with controls; however, the differences in both parameters failed to reach statistical significance. The body mass index values and waist circumference of the patient group were significantly higher than controls (p=0.003 and p=0.002, respectively). Fasting serum insulin levels and Homeostasis Model Assessment scores of patients with colorectal adenoma were significantly higher than those of controls (p=0.02 and p=0.02, respectively). There was no relation between the number of colorectal adenomas and serum adiponectin or resistin levels. Conclusion: Our data indicate that obesity and insulin resistance may contribute to the development of colorectal adenoma and that serum adiponectin levels and insulin resistance may not have a substantial predictive value for colorectal adenoma.